The coming death : traces of mortality across East Asia - Calichman, Richard (Albany : State University of New York Press, 2022)
"Explores questions of death and mortality in several key texts of East Asian literature and cinema"--
Lines of mortality in Kurosawa Akira's Ikiru -- Tsai Ming-liang and the Time of survival -- From culture to finitude : the question of Death in Takeuchi Yoshimi's reading of Lu Xun -- Interlacings of nothing : the question of death in Takeuchi Yoshimi's reading of Lu Xun II.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on March 25, 2022).
JSTOR
Keywords: Death in motion pictures; Mortality in motion pictures; Death in literature; Mortality in literature; Motion pictures -- East Asia -- History; East Asian literature -- History and criticism; Mort au cinéma.; Mortalité au cinéma.; Mort dans la littérature.; Mortalité dans la littérature.; Littérature extrême-orientale -- Histoire et critique; SOCIAL SCIENCE / Ethnic Studies / Asian Studies; Death in literature; Death in motion pictures; East Asian literature; Mortality in literature; Mortality in motion pictures; Motion pictures; East Asia; Criticism, interpretation, etc; History